Analysis of direct medical costs in inpatient treatment of diabetic foot ulcers at Nhan Dan Gia Dinh Hospital in 2024 - 2025 - Loc, Nguyen Van; Nguyet, Pham Minh; Thap, Dang The; Thuy, Nguyen Thi Thu; Dung, Pham Van (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Introduction: Diabetic foot ulcer (DFU) is one of the most serious and common complications in patients with diabetes mellitus Its treatment is typically is prolonged, complex, and costly. Identifying direct medical costs (DMC) is essential for effective financial planning and healthcare resource management. Methods: A cross-sectional descriptive study was conducted using retrospective data extracted from medical records and treatment cost statements of patients with diabetic foot ulcers (DFUs) who met the sampling criteria at Nhan Dan Gia Dinh Hospital during the 2024 - 2025 period. Results: A total of 143 inpatient DFU treatment episodes were included. The male-to-female ratio was 1.04:1 and the majority of patients were elderly (83.9%). The average DMC was 24,319,384 VND (95% CI: 17,981,415 - 30,657,353 VND), with health insurance most of the cost (71.39%) and medication costs accounted for the highest proportion (43.10%). The multivariate regression model demonstrated significant associations between DMC and related factors, expressed as (Adjusted R² = 0.650; p < 0.001): LogDMC = 0.709 × “length of stay” + 0.154 × “chronic kidney disease” - 0.131 × “amputation” + 0.123 × “ulcer severity” + 6.784. Conclusions: During 2024 - 2025, the average DMC for a DFU inpatient episode at Nhan Dan Gia Dinh Hospital was 24.3 million VND (450% of the 2024 average monthly income), with health insurance coverage and medication costs representing the largest proportions. The study identified length of hospital stay as the strongest predictor of treatment costs; therefore, healthcare facilities should prioritize strategies to shorten hospitalization through optimized treatment regimens, enhanced clinical management, and improved care processes to achieve more effective cost control.